2004
DOI: 10.1016/j.prrv.2004.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of rhinovirus-induced asthma

Abstract: Several epidemiological studies using sensitive detection methodologies have confirmed that the majority of acute asthma exacerbations follow upper respiratory tract infections--common colds. Most of these colds are due to human rhinoviruses (RVs). RVs are able to reach and replicate in epithelial cells of the lower airways and can activate these cells to produce pro-inflammatory mediators. Under some circumstances, RVs can also become cytotoxic to the epithelium. Atopic asthmatic individuals produce less inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 48 publications
0
49
0
1
Order By: Relevance
“…Furthermore, despite strong epidemiological evidence supporting the role of RV in the pathogenesis of asthma, airway reactivity and airflow limitation, the underlying mechanisms are unclear. Although damage to the developing airways and altered immune responses are thought to be the main mechanisms through which RV could induce asthma and airway hyperreactivity later in life [107,108], others have suggested that early-life infection with RV might be the first indication of the pre-existing tendency in some children to develop asthma, including among preterm infants [109,110]. The ability of RV to induce prolonged and exaggerated inflammatory responses after the initial infection has been described as a potential contributor to the development of chronic respiratory morbidity among preterm infants, with limited data demonstrating increased airway secretion of inflammatory cytokines and remodelling molecules during acute RV infection, particularly among those with BPD [108,111].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Furthermore, despite strong epidemiological evidence supporting the role of RV in the pathogenesis of asthma, airway reactivity and airflow limitation, the underlying mechanisms are unclear. Although damage to the developing airways and altered immune responses are thought to be the main mechanisms through which RV could induce asthma and airway hyperreactivity later in life [107,108], others have suggested that early-life infection with RV might be the first indication of the pre-existing tendency in some children to develop asthma, including among preterm infants [109,110]. The ability of RV to induce prolonged and exaggerated inflammatory responses after the initial infection has been described as a potential contributor to the development of chronic respiratory morbidity among preterm infants, with limited data demonstrating increased airway secretion of inflammatory cytokines and remodelling molecules during acute RV infection, particularly among those with BPD [108,111].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…This observation was associated with increased paracellular permeability, effects that appear to be related to viral replication in immortalised cell lines grown as polarised monolayers [133], but may be amplified by pro-inflammatory cytokines [134]. In experimental and naturally occurring HRV-induced infection, airway epithelial cell and inflammatory-immune effector cell activation has been described with cytokines, chemokines and growth factor production associated with increased release of histamine and eosinophil cationic protein [135][136][137][138][139]. Recruitment of neutrophils, eosinophils, mast cells and CD4 + and CD8 + T-cells has been demonstrated through increased release of IL-6, IL-8, IL-16, IFN-γ-induced protein-10, eotaxin, RANTES, leukotrienes and other pro-inflammatory cytokines [137,140,141].…”
Section: Rhinovirus Infection and Asthma Inductionmentioning
confidence: 99%
“…RV infection activates inflammatory pathways by increasing levels of neutrophils, eosinophils, CD4+ cells, CD8+ cells and mast cells through increased mRNA expression and translation of IL-6, IL-8, IL-16, eotaxin, interferon (IFN)-c-inducible protein (IP) 10, CC chemokine ligand 5 (RANTES) and other pro-inflammatory cytokines and chemokines [66]. Moreover, viruses generate systemic as well as neural responses, further inducing inflammation and hyperresponsiveness.…”
Section: Mechanisms Of Virus-induced Exacerbationmentioning
confidence: 99%